Edukasi Bahaya Bahan Kimia Obat Yang Terdapat di Dalam Obat Tradisional Desa Jagasima Klirong Kebumen - Titi Pudji Rahayu; Muh.Husnul Khuluq; Laeli Fitriyati (Prosiding University Research Colloquium, 2022)
The wrong use of traditional medicine is when people have expectations that traditional medicine can heal, so their use increases. This Community Service was carried out in Jagasima Village, Klirong District, targeting PKK cadres and villagers. The problem that arises is the lack of public knowledge about traditional medicines that contain medicinal chemicals and without knowing traditional medicines there is no distribution permit from BPOM. This community service aims to realize accuracy, care, awareness, understanding and increase knowledge in using traditional medicines correctly and understanding the dangers of medicinal chemicals in traditional medicines so as to be able to provide explanations and increase knowledge to the public on the use of traditional medicines so that a drug-aware society is realized. The method used was data collection of prospective trainees, discussions with village officials and committees formed by the village, discussions with members, implementation of activities in the form of lectures, discussions, ice breaking and simulations related to traditional medicines and medicines. In conclusion, the community in Jogosima Village as the target was very enthusiastic in participating in this activity. After this activity, the village community can know the dangers of medicinal chemicals found in traditional medicines and can know how to choose good and correct traditional medicines that do not contain medicinal chemicals.